The Relationship Between Smoking and Blood Glucose Levels in Active Smoking Fishermen in Banggae Sub-District, Majene District - Zulkifli, Andi Aldita Nitamapia; Safitri, Asrini; Hamzah, Pratiwi Nasir; Iskandar, Darariani; Gayatri, Sri Wahyuni (Faculty of Medicine, Universitas Tadulako, 2025)
Background: Smoking is a major risk factor for non-communicable diseases such as diabetes mellitus, and fishermen may have specific smoking habits that influence blood glucose levels. Objective: To analyze the relationship between smoking activity and random blood glucose levels among active fishermen in Banggae Sub-District, Majene District. Methods: This quantitative analytical study with a cross-sectional design involved 100 active fishermen selected using the Slovin formula, with data analyzed using Spearman correlation in SPSS. Results: Most respondents were young (45%) and middle-aged adults (46%), and 94% smoked filter cigarettes. A significant positive correlation was found between smoking activity and random blood glucose levels (r = 0.295, p = 0.003), indicating that higher smoking frequency and dependency were associated with elevated glucose levels. Conversely, no significant relationship was observed between dietary patterns and glucose levels (r = -0.081, p = 0.422). These findings suggest that smoking intensity, rather than food type, plays a more dominant role in glucose dysregulation among fishermen. Conclusion: Increased smoking activity is significantly correlated with higher random blood glucose levels, emphasizing the urgent need for smoking cessation interventions to reduce diabetes risk in this high-risk occupational group.